Joint effects of the epigenetic alteration of neurotrophins and cytokine signaling: a possible exploratory model of affective symptoms in alcohol-dependent patients? - Heberlein, Annemarie; Schuster, Rilana (Alcohol and alcoholism, 2017)
Methods: In this study we investigated a possible association between alterations in the methylation of the BDNF IV/NGF I gene promoter and the cytokines tumor necrosis factor α (TNF-α) and interleukin-6 (IL-6) in 55 male alcohol-dependent patients. Results: Mean methylation of the promoter of the BDNF gene was signiﬁcantly associated with the TNF-α serum levels and the CIWA-score during withdrawal (P < 0.001). Moreover, mean methylation of the NGF I promoter was signiﬁcantly associated with the IL-6 serum levels and STAI-I score during withdrawal (P < 0.001). Conclusion: Our results suggest an association between the epigenetic regulation of both neurotrophins, BDNF and NGF, cytokine release and the symptomatology of alcohol dependence. They imply that changes in the methylation of neurotrophins may contribute to the symptomatology of alcohol dependence by affecting relevant downstream signaling cascades.